Uncertainty of sound insulation measurement in laboratory - Tadeusz Wszołek (Archives of Acoustics)
Protection against noise is one of the six essentials requirements of the European Union directive. In buildings airborne sound insulation is used to define the acoustic quality of walls between rooms. However the evaluation of sound insulation /index/ is sometimes difficult or even ambiguous, both in field and laboratory measurements, in spite of the fact that there are some unified measurement procedures specified in the ISO 140 standards. There are problems with the reproducibility and repeatability of the measurement results. Some difficulties may be caused by non-diffuse acoustic fields, non uniform reverberation time or errors of the reverberation time measurements. Some minor problems are also posed by flanking transmission and the S/N ratio. The paper includes an analysis of partial uncertainties of the above mentioned measurement components and their influence on the combined uncertainty in 1/3 octave frequency bands and the sound reduction index determined according to ISO 140-3, using the uncertainty propagation law. All of the analysis and calculations performed in the paper concern the conjugated reverberation rooms and measurement set-up located in AGHUST Department of Mechanics and Vibroacoustics in Kraków.